Two new brackish-water species of Pogaina (Rhabdocoela: Provorticidae) from China - Zhong, Lin-Hong; Xie, Yao-Hang; Hu, Xiao-Zhou; Chen, Yu-Si; Feng, Wei-Tao; Zhang, Yu; Wang, An-Tai (Zootaxa, 2019)
Two new species of the genus Pogaina Marcus, 1954 (Provorticidae), namely Pogaina sinensis n. sp. and Pogaina shenzhenensis n. sp. are described from brackish water in the intertidal zone of Shenzhen Bay. For P. sinensis n. sp., the tubular stylet is slightly curved at the distal end and a fusiform structure with a flange is present at 66% of the stylet. The flange encircles the stylet, with its ends attached to the midpoint and the distal end of the stylet. For P. shenzhenensis n. sp., the stylet has a N-shaped overall morphology. A band provided with dense needle-like structures is present at the distal end of the stylet. Both the morphological (stylet) and phylogenetic (18S rDNA and 28S rDNA) analyses support the establishment of these two new species.